2011
DOI: 10.1007/s10584-011-0036-6
|View full text |Cite
|
Sign up to set email alerts
|

Rainfall characteristics for periglacial debris flows in the Swiss Alps: past incidences–potential future evolutions

Abstract: Based on observational meteorological data since A.D. 1864 and tree-ring records of debris-flow activity, this paper assesses changes in rainfall characteristics and their impact on the triggering of geomorphic events in a high-elevation watershed of the Swiss Alps since the end of the Little Ice Age. No trends are visible in the frequency of heavy rainfall events, but we observe a reduced number of heavy, shortlived rainfalls in summer and a concentration of advective storms is recorded in late summer and ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 103 publications
(66 citation statements)
references
References 68 publications
3
61
0
2
Order By: Relevance
“…The top classifications are all automated, while the best of the subjective classifications are highlighted in the shaded rows. Rank is based on the BSS result, name is from the COST733 catalogue often associated with convective storms and heavy downpours in the region (Rudolph and Friedrich 2011;Stoffel et al 2011) potentially causing the high landslide numbers observed. In contrast, the anticyclone over central Europe (type #18; Fig.…”
Section: Cost733 Synoptic Weather Types and Landslide Occurrencementioning
confidence: 99%
“…The top classifications are all automated, while the best of the subjective classifications are highlighted in the shaded rows. Rank is based on the BSS result, name is from the COST733 catalogue often associated with convective storms and heavy downpours in the region (Rudolph and Friedrich 2011;Stoffel et al 2011) potentially causing the high landslide numbers observed. In contrast, the anticyclone over central Europe (type #18; Fig.…”
Section: Cost733 Synoptic Weather Types and Landslide Occurrencementioning
confidence: 99%
“…Since Pinus spp. has a different genetic setup and does not generate tangential rows of resin ducts (or TRD; Stoffel, 2008) after mechanical damage, these species could not be used as a proxy to infer the seasonality of flash flood events (Stoffel and Beniston, 2006;Stoffel et al, , 2011. Flash flood seasonality has instead been inferred from those samples showing wound borders on the increment rings and from a comparison between damage and meteorological record.…”
Section: Dendrogeomorphic Analysismentioning
confidence: 99%
“…Inhabitants and visitors in the Matter Valley (Switzerland, Valais) are threatened by various natural hazard processes; moreover, an observed change in the frequency of debrisflow events enhances this peril (Graf and McArdell, 2005;Stoffel et al, 2011;. The Dorfbach torrent case study is based on the assessment of one of these hazardous torrents in the Matter Valley (Fig.…”
Section: Research Areamentioning
confidence: 99%